Pengaruh Dukungan Sosial dan Efikasi Diri terhadap Kualitas Hidup Dimediasi dengan Resiliensi pada Pasien Lansia Hipertensi di Puskesmas Nanggalo Padang - Fransiska Paska; Mulya Virgonita (Pusat Riset dan Inovasi Nasional, 2026)
This study is motivated by the high prevalence of hypertension among the elderly and the complexity of psychosocial factors that influence their quality of life. The purpose of this research is to analyze the influence of social support and self-efficacy on the quality of life of elderly individuals with hypertension, with resilience as a mediating variable. The research employed an explanatory quantitative design with a sample of 122 elderly individuals with hypertension at Puskesmas Nanggalo Padang selected through accidental sampling. Data were collected using a Likert-scale questionnaire that had been tested for validity and reliability, and then analyzed using SEM-PLS through SmartPLS to examine the structural relationships among variables. The results indicate that social support and self-efficacy positively affect quality of life, both directly and indirectly through resilience as a mediator, demonstrating that these three variables complement one another in enhancing the adaptive capacity of elderly individuals facing chronic conditions. These findings imply that psychosocial-based interventions, such as strengthening family support, enhancing self-efficacy, and providing resilience training, need to be developed in primary healthcare services to improve the quality of life of elderly individuals with hypertension.